RANCANGBANGUN ALAT PENGHITUNG BENIH IKAN MENGGUNAKAN SENSOR OPTIK FOTOTRANSISTOR BERBASIS MIKROKONTROLER ATMEL ATMEGA8 - , WIDAGDO PURBOWASKITO, Ir. R. Handoyo, M.Eng ([Yogyakarta] : Universitas Gadjah Mada, 2014)
A problem in the fish germ trading activity is the counting process of fish germ numbers are still done manually. Manual counting process of fish germ takes a long time and it done inaccurately. The fish germ counter is expected to solve or alleviate this problem. The fish germ counter design is consist of two integrated systems such as electronics systems and mechanical systems. The electronics systems are consist of phototransistor optical sensor, Atmel ATMega8 microcontroller, and display LCD. The Electronics systems are supported by mechanical systems such as a plastic tub, three PVC pipes, three transparent pipes, and an iron frame. The fish germ counter trial result showed that the best accuracy on the 5/8 inch diameter transparent pipe used is 91.2 % with 8.8 % error. The fish germ counter capacity is 75 fishes/minutes. The fish germ counter is not physically harms the fish germ.